EFFECT OF PROTECTED INDIAN SARDINE (Sardinella longiceps) OIL, PALM OIL, AND PALM KERNEL CAKE INTAKE ON DIGESTIBILITY OF DRY MATTER, ORGANIC MATTER, AND CRUDE PROTEIN BY RUMEN FLUID OF FISTULAE ONGOLE BREED CATTLE - Susi Dwi Widyawati, Catur Suci Purwati Wara Pratitis S.S & (Proceeding of International Congress, 2014)
Livestock business, ruminant in particular, has been growing rapidly with the increased demand ofhigh quality food ingredient, such as meat and dairy products. However, digestion process in ruminants isrelatively more complicated compare to other animals. Carbohydrate is the main energy source and fat asthe alternate, both from vegetable and animalâs fat. This study aimed to determine the effect of protectedIndian sardine fish oil, palm oil, and palm kernel cake consumption on digestibility of dry matter, organicmatter, and crude protein by rumen fluid of fistulae Ongole breed cattle. Latin square experiment designwas applied on 3 treatments. Fermented rice straw (FRS), basal concentrate (BC), and protected materialsof Indian sardine oil (ISO), palm oil (PO), and palm kernel cake (PKC) were used as feed ingredient.Treatments were: P1 = FRS 40% + BC 60 % (BC 95% + PO 5%) ; P2 = FRS 40% + BC 60% (BC 95 % + ISO5%) ; P3 = FRS 40% + BC 60 % (BC 90% + PKC 10%). Analyzed parameters were intake and digestibility ofdry matter, organic matter, and crude protein, and also digestible nutrient of organic matter (DN OM)and crude protein (DN CP). The results showed that average dry matter intake of P1, P2, P3 were 6108.77;5965.87; 5686.78 (g/head/day), organic matter intake were 5658.19; 5569.29; 5603.11 (g/head/day), proteinintake were 690.58; 829.84; 818.15 (g/head/day), dry matter digestibility were 54.55; 54.00; 54.23 (%),organic matter digestibility were 66.09; 66.59; 64.00 (%), crude protein digestibility were 81.77; 80.48;79.73 (%), DN OM were 61.33; 62.06; 63.06 (%), and DN CP were 10.69; 10.34; 10.82 (%), respectively.Analysis of variance showed no significant difference between intake and digestibility of dry matter,organic matter, crude protein, DN OM, DN CP (P > 0.05) among treatments. It was concluded thatconsumption of 5% Indian sardine oil, 5% palm oil, and 10% palm kernel cake protected materials did notaffect of dry matter, organic matter, and crude protein digestibility in fistulae Onggole Crossbreed rumen.Keywords: Ongole grade cattle, Indian sardine oil, palm oil, and palm kernel cake, digestibility